A Comparative Study of Merger Effect on Financial Performance of Banking and Financial Institutions in Nepal - Shrestha, Magina; Thapa, Ram Kumar; Phuyal, Ram Kumar (Journal of Business and Social Sciences Research, 2018)
Merger and Acquisition is relatively new reorganization practice undertaken to strengthen the BFIs in the Nepalese financial market. This study makes an attempt to analyze the financial performance of merged banking and financial institutions relative to their pre-merger performance, and assess the perception of the stakeholders towards merger. Six banks and financial institutions are considered as sample to undertake this study along with 120 respondents for secondary and primary data respectively. The financial ratios comparison method along with t-test of changes in performance measures has been used. This study found that merger impacts performance positively when larger and stable parties such as commercial banks act as bidders as opposed to the merger between smaller BFIs mainly other than commercial banks as bidder. The loan quality significantly deteriorates after merger in most of the cases and profitability measured in terms of ROA and ROE is adversely affected in most of the cases after the merger. Therefore, the merger should not be considered as the definite solutions to overcome the challenges faced in the market; enough evaluation is needed to select the right partners before executing the merger. Journal of Business and Social Sciences Research, Vol. 2, No. 1 & 2, pp. 47-68